Extraction, purification, structural elucidation, and immunomodulatory activity of Bletilla striata polysaccharides via the NF-κB signaling pathway - Pang, Guofeng; Zhou, Kai; Gao, Di; Wang, Danli; Xue, Juan; Lu, Tian; Chai, Huifang (Frontiers in Immunology, 2026)
IntroductionBletilla striata is a traditional medicinal plant, and its polysaccharide components have been confirmed to possess immunomodulatory potential. However, most current studies focus on high-molecular-weight polysaccharides, while the immunomodulatory mechanism of low-molecular-weight polysaccharides from this plant remains unclear. This study aimed to isolate and identify a low-molecular-weight polysaccharide (BSP-2) from B. striata tubers, and to explore its immunomodulatory activity as well as the related action mechanism.MethodsA neutral polysaccharide (BSP-2) was isolated from B. striata tubers. Its molecular weights were characterized using high-performance gel permeation chromatography (HPGPC) and nuclear magnetic resonance (NMR); its monosaccharide composition was determined via component analysis. The immunomodulatory activity of BSP-2 was evaluated using lipopolysaccharide (LPS)-stimulated RAW264.7 cells (by detecting pro-inflammatory mediator production), and its mechanism was investigated through the analysis of relevant protein expressions.ResultsBSP-2 exhibited the following molecular weight parameters: number-average (3.612 ± 0.13646 kDa), weight-average (4.456 ± 0.18019 kDa), z-average (6.364 ± 0.5518 kDa), and peaked molecular weight (2.808 ± 0.09041 kDa). Component analysis revealed that BSP-2 was dominated by glucose (Glc), with minor proportions of galactose (Gal), arabinose (Ara), and rhamnose (Rha) residues. In LPS-stimulated RAW264.7 cells, BSP-2 inhibited the production of four pro-inflammatory mediators: IFN-γ, TNF-α, IL-1β, and IL-6. Mechanistically, the anti-inflammatory effects of BSP-2 were mediated by the regulation of the NF-κβ pathway, which involved the downregulation of proteins including p65, p-p65, IκBα, p-IκBα, COX-2, and iNOS.DiscussionThese results demonstrate that BSP-2 balances pro-inflammatory responses via the NF-κB pathway, supporting its promising application as a bioactive immunoregulatory component in functional food and dietary supplement development.